A novel Ba0.95La0.05Fe0.9Nb0.1O3−δ ceramic electrode for symmetrical solid oxide fuel cells. Issue 23 (27th October 2021) - Li, Zhongbiao; Wang, Jinpeng; Zhu, Jiangpeng; Sun, Yanjun; Wang, Zhihao; Zhao, Yujun; Wei, Zhaoling; Zhu, Zhiwen; Zheng, Qiuju
Abstract : The Ba0.95 La0.05 Fe0.9 Nb0.1 O3− δ electrode provides a unique combination of good tolerance for H2 -reduction and low polarization resistances for the oxygen reduction reaction and hydrogen oxidation reaction. Abstract : There are few reports about symmetrical electrodes based on BaFeO3− δ -parent oxides. In this study, a novel Ba0.95 La0.05 Fe0.9 Nb0.1 O3− δ (BLFN) ceramic electrode is developed for use as an electrode for symmetrical solid oxide fuel cells (S-SOFCs). The X-ray diffraction (XRD) result reveals that the Nb dopant can keep the cubic perovskite structure of the BLFN material stable against wet hydrogen reduction due to the steady valence state of Nb and the strong Nb–O bond. The maximum electrical conductivities of the BLFN material are 4.91 and 1.58 S cm −1 in air and 5% H2 /Ar, respectively. Electrochemical impedance spectra (EIS) studies discovered the outstanding catalytic activity of the BLFN electrode toward the hydrogen oxidation reaction and oxygen reduction reaction. Polarization resistances at 750 °C are as low as 0.055 and 0.148 Ω cm 2 in air and hydrogen, respectively, far lower than those of reported symmetrical electrodes. The analysis of the distribution of relaxation times (DRT) for EIS under different P O2 and P H2 indicates that the rate-limiting steps of the BLFN electrode are determined by the hydrogen adsorption/dissociation process for the anode and the dissociation of adsorbed oxygen for the cathode, respectively. The single S-SOFC achieves a high peak power density of 581 mW cm −2 and low polarization resistance of 0.096 Ω cm 2 at 800 °C. These results indicate that the BLFN material is a potential candidate for S-SOFC electrode applications.